2022
DOI: 10.1186/s12933-022-01572-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of GLP-1 receptor agonists versus SGLT-2 inhibitors in type 2 diabetes: an Italian cohort study

Abstract: Background GLP-1 receptor agonists (GLP-1 RA) and SGLT-2 inhibitors (SGLT-2i) have shown to reduce the risk of major adverse cardiovascular events (MACE), death and worsening nephropathy when added to standard of care. However, these two dug classes differ in efficacy and safety. We compared the effectiveness and safety profile of GLP-1 RA and SGLT-2i in a large and unselected cohort of patients with type 2 diabetes resident in Lombardy from 2015 to 2020. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Baviera et al's study ( 1 ) showed that in T2D patients without previous cardiovascular disease (CVD) GLP1RAs vs. SGLT2is were associated with lower risks of MACE-3 [HR (95% CI): 0.87 (0.80, 0.96)], MACE-4 [HR (95% CI): 0.90 (0.83, 0.98)], and ACM [HR (95% CI): 0.88 (0.79, 0.98)]; and similar risk of HHF [HR (95% CI): 1.03 (0.87, 1.23)]. On the contrary, Lin et al's network meta-analysis ( 8 ) showed that in T2D patients without previous CVD SGLT2is vs. GLP1RAs had similar risk of MACE [HR (95% CI): 0.93 (0.73, 1.19)].…”
Section: Substantial Differences In T2d Subgroupsmentioning
confidence: 91%
See 4 more Smart Citations
“…Baviera et al's study ( 1 ) showed that in T2D patients without previous cardiovascular disease (CVD) GLP1RAs vs. SGLT2is were associated with lower risks of MACE-3 [HR (95% CI): 0.87 (0.80, 0.96)], MACE-4 [HR (95% CI): 0.90 (0.83, 0.98)], and ACM [HR (95% CI): 0.88 (0.79, 0.98)]; and similar risk of HHF [HR (95% CI): 1.03 (0.87, 1.23)]. On the contrary, Lin et al's network meta-analysis ( 8 ) showed that in T2D patients without previous CVD SGLT2is vs. GLP1RAs had similar risk of MACE [HR (95% CI): 0.93 (0.73, 1.19)].…”
Section: Substantial Differences In T2d Subgroupsmentioning
confidence: 91%
“…Taken together, GLP1RAs vs. SGLT2is can reduce more stroke events (GLP1RAs: 17% reduction; SGLT2is: cannot reduce stroke), and SGLT2is vs. GLP1RAs can reduce more HHF events (SGLT2is: 31% reduction; GLP1RAs: 11% reduction). However, Baviera et al's study ( 1 ) showed no difference between GLP1RAs and SGLT2is in the risks of stroke and HHF.…”
Section: Substantial Differences In Stroke and Hhfmentioning
confidence: 96%
See 3 more Smart Citations